Female pelvic floor myofascial syndrome and its relationship with lower urinary tract storage symptoms - Leyva Vazquez, José I.; Guerrero Reyes, Guadalupe; Gutiérrez González, Adrián; Hernández Velázquez, Ricardo; Loya Maldonado, Karen M.; Treviño Cavazos, Omar; Reyes Alcaraz, Jennifer E.; Robledo Torres, Alejandra; Saca Cuevas, Sara Y.; Herrera Morales, Juan C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pelvic floor myofascial syndrome is defined as non-articular skeletal muscle pain, characterized by the presence of trigger points. Present in 14-23% of patients with chronic pelvic pain. It has an impact on urinary function. The prevalence of lower urinary tract symptoms is 15-67%, with storage symptoms predominating in patients with PFMS. Objective was to determine the relationship between female pelvic floor myofascial syndrome and lower urinary tract storage symptoms. Methods: This was a retrospective, observational, descriptive, cross-sectional, homodemic and single-center study at University Hospital Doctor José Eleuterio González, Monterrey, Nuevo Leon, Mexico from period one from April 1st to June 30th, 2022. Type of non-probabilistic convenience sampling. Database in Excel 2016, Pearson’s Х² statistical test in the SPSS V25® program. Results: 136 patients with PFMS and LUTS storage were evaluated. The most frequent age group was 46-55 years with 33.1% (N=45); the marital status was married with 74.3% (N=101). In relation to education 55.9% (N=76) with a bachelor’s degree. The most frequent storage symptoms were nocturia 67.6% (N=92) p<0.05, frequency 60.3% (N=82) p=0.512, urgency 57.4% p<0.005. Conclusions: Knowing the correlation between PFMS and storage LUTS can guide specific pain treatment with review of urinary symptoms. In patients with nocturia, frequency, urgency, SUI and UUI, a physical examination should be performed and included trigger points in the pelvic floor. Nocturia is the most prevalent storage LUTS in PFMS.